Communication In Pesantren Educational Institutions: The Application Of Social Cognitive Theory In Understanding Social Interaction In The Pesantren Environment - M Rizqi Fajrul Falah; Hasan Baharun; Adi Wibowo; Shofa Aulia Kumala (Mapendis: Jurnal Manajemen Pendidikan Islam, 2023)
The purpose of this research is to understand how the learning process occurs in the Nurul Jadid Islamic Boarding School environment through social interaction. The approach used in this research is qualitative with descriptive type. as for the informants of this study consisted of santri, teachers, kyai. the data collection technique used interviews, participatory observation and documentation study. data analysis used in this research is hubermen analysis which consists of several stages, namely data reduction, data presentation and conclusion drawing. The results of this study indicate that Learning Through Observation which consists of Learning Through the Process of Paying Attention, Learning Through the Process of Remembering, Learning Through the Process of Production, Learning Through the Process of Motivation, Application of Social Learning Principles in Pesantren. Sharpening Social Skills, Fostering Tolerance and Harmony, Instilling Ethics and Morals, Encouraging Collaborative Learning, Providing Valuable Life Experience research provides an impact or implication in relation to social interaction among students.